Pelatihan Penggunaan Aplikasi Mendeley Bagi Guru Sekolah Dasar (SD) di Kabupaten Jeneponto - Akhyar Muchtar; Hilda Ashari; Sari, Dessy Ana; Elfira Makmur; Muh. Iswal Burhan (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
This Community Partnership Program (PKM) partner is SD Negeri 13 Allu. The problems are: (1) teachers lack knowledge about the concept of citation in scientific work,(2) teachers have doubts about writing reading sources as a reference for research writing, (3) the citation system has so far been done manually, and (4) teachers have not been able to use the reference creation application automatically. The external goal is scientific work that is more systematic and coherent in citing reference sources. The methods used are lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners know the concept of citing in scientific work, (2) partners have the skills to write reference sources appropriately, (3) partners can use developing technology, especially in writing references automatically, (4) teachers have skills using Mendeley's application in writing scientific papers.